MAKNA PERAN GENDER BAGI WANITA PENGUSAHA SONGKET PUSAKO MINANG PANDAI SIKEK - Freddy, Jihan Layla; Yanladila Yeltas Putra (CAUSALITA : Journal of Psychology, 2024)
Gender issues are one of the many problems faced by women which are related to the way men and women are viewed from a non-biological perspective. Traditionally there is a view that men can fulfill their desires while women cannot. The thing that underlies the emergence of certain preferences for gender stereotypes or gender roles is attitude. Attitudes are basically subjective and individual, so there is a high possibility of differences that can lead to conflict or division. How a person responds to this is called gender role attitudes. This research aims to describe and explain how the owner of Pusako Minang interprets her gender role as a minang woman and as a woman entrepreneur. The data collected from this research were obtained through in-depth interviews with owner songket Pusako Minang Pandai Sikek. The data obtained was then analyzed and validated using the method proposed by Miles and Huberman. In this research, three themes were found, namely the business undertaken, women entrepreneurs and gender role attitudes. The first theme consists of entrepreneurial motivation, songket business, the ups and downs of business and the principles of entrepreneurship. The second theme consists of the journey to becoming an entrepreneur, the benefits of becoming an entrepreneur, and the characteristics of entrepreneurs. The third theme is gender role attitudes which consist of gender roles, maintaining ancestral heritage, the benefits of weaving skills, life principles, and dual roles.